Moral Values That Thwart Intergroup Interactions: An Investigation on the Interaction Between Indonesian Moslems and Chinese-Indonesian Christians - Hudiyana, Joevarian; Muluk, Hamdi; Milla, Mirra Noor (UI Scholars Hub, 2017)
As one of the most established theories, the contact hypothesis has been well-researched throughout decades of investigations. However, there have been few attempts to investigate individual factors that may influence interaction processes that may lower prejudice. The present study attempts to find the individual factors that can moderate the contact – prejudice effect, that is, individual moral values. Previous researches have noted that individuals with high moral loyalty, authority, and sanctity may resist interacting with outgroups. Consequently, these individuals may possess higher prejudice. Thus, we hypothesize that individuals with higher levels of those three moral values may experience the contact effect more profoundly, in which there is stronger contact – prejudice effect. 594 Moslem participants participated in the online survey we administered. We found that moral authority and purity can moderate the contact – prejudice effect, consistent with our hypotheses. These patterns were found only for the contact – subtle prejudice effect. However, moral loyalty cannot moderate this effect. We discuss the implications by examining the Indonesian current sociopolitical conditions and how the three moral values influence the dynamics of intergroup contact.